Tenofovir concentrations in hair strongly predict virologic suppression in breastfeeding women. (1st August 2019) - Murnane, Pamela M.; Bacchetti, Peter; Currier, Judith S.; Brummel, Sean; Okochi, Hideaki; Phung, Nhi; Louie, Alexander; Kuncze, Karen; Hoffman, Risa M.; Nematadzira, Teacler; Soko, Dean K.; Owor, Maxensia; et al.
Abstract : Background: Antiretroviral treatment (ART) adherence is often suboptimal in the perinatal period. We measured hair tenofovir (TFV) concentrations as a metric of adherence in postpartum women to understand patterns and predictors of adherence throughout this critical period. In addition, we examined the association between hair TFV concentrations and virologic outcomes. Methods: Between 12/2012 and 09/2016, hair samples were collected longitudinally from delivery through breastfeeding from women on ART in the Promoting Maternal and Infant Survival Everywhere study (NCT01061151) in sub-Saharan Africa. Hair TFV levels were measured using validated methods. Using generalized estimating equations, we estimated the association between hair TFV levels and virologic suppression (<400 copies/ml) over time and assessed predictors of hair TFV levels. Results: Hair TFV levels were measured at 370 visits in 71 women from delivery through a median of 14 months (interquartile range 12–15) of breastfeeding. Levels ranged from below detection (0.002) to 1.067 ng/mg (geometric mean: 0.047). After at least 90 days on ART, 69 women had at least one viral load measured (median 5 measures, range 1–9); 18 (26%) experienced viremia at least once. Each doubling of TFV level more than doubled odds of concurrent virologic suppression [odds ratio 2.35, 95% confidence interval (CI): 1.44–3.84, P = 0.0006] and was associated with 1.43 times the odds of future suppression (95% CI: 0.75–2.73, P = 0.28). Relative to the first 3 months after delivery, hair levels were highest in months 6–12 (1.42-fold higher, 95% CI: 1.09–1.85, P = 0.01). Conclusion: Hair TFV levels strongly predicted concurrent virologic suppression among breastfeeding women. Objective adherence metrics can supplement virologic monitoring to optimize treatment outcomes in this important transition period.